2017
DOI: 10.1111/bjh.14543
|View full text |Cite
|
Sign up to set email alerts
|

Treatment burden, haemostatic strategies and real world inhibitor screening practice in non‐severe haemophilia A

Abstract: Inhibitor formation in non-severe haemophilia A is a life-long risk and associated with morbidity and mortality. There is a paucity of data to understand real-world inhibitor screening practice. We evaluated the treatment burden, haemostatic strategies, F8 genotyping and inhibitor screening practices in non-severe haemophilia A in seven London haemophilia centres. In the 2-year study period, 44% (377/853) patients received at least one haemostatic treatment. Seventy-nine percent of those treated (296/377) rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 30 publications
4
38
0
1
Order By: Relevance
“…A previous cohort study in Italy, performed by Tagliaferri et al, found a mean ABR of 0.56 (SD ± 0.67) for patients with mild hemophilia A. These results are in line with our own findings of a median ABR of 0.8 (interquartile range, 0.3‐2.5) in patients with mild hemophilia A from the INSIGHT study (unpublished data) and other previously published studies of patients with nonsevere hemophilia A, reporting an ABR of 0.5‐0.6 . In the Italian cohort, most patients experienced mucocutaneous bleeds (80%), followed by muscle bleeds (34%) and joint bleeds (31%).…”
Section: Bleeding Phenotype In Nonsevere Hemophiliasupporting
confidence: 90%
See 1 more Smart Citation
“…A previous cohort study in Italy, performed by Tagliaferri et al, found a mean ABR of 0.56 (SD ± 0.67) for patients with mild hemophilia A. These results are in line with our own findings of a median ABR of 0.8 (interquartile range, 0.3‐2.5) in patients with mild hemophilia A from the INSIGHT study (unpublished data) and other previously published studies of patients with nonsevere hemophilia A, reporting an ABR of 0.5‐0.6 . In the Italian cohort, most patients experienced mucocutaneous bleeds (80%), followed by muscle bleeds (34%) and joint bleeds (31%).…”
Section: Bleeding Phenotype In Nonsevere Hemophiliasupporting
confidence: 90%
“…26 and other previously published studies of patients with nonsevere hemophilia A, reporting an ABR of 0.5-0.6. 28,29 In the Italian cohort, most patients experienced mucocutaneous bleeds (80%), followed by muscle bleeds (34%) and joint bleeds (31%). When we focus on the annual joint bleeding rate (AJBR), a rate of 0.08 (SD ± 0.26) is seen in the cohort study of Tagliaferri et al 27 In contrast, a recent study performed in the United States by Soucie et al, demonstrated a higher AJBR of 0.97 in patients with mild hemophilia A.…”
Section: Diagnosis Of Nonsevere Hemophiliamentioning
confidence: 99%
“…In this issue of British Journal of Haematology , Batty et al () present remarkable documentation of “real world” inhibitor screening practices in patients with non‐severe haemophilia A, which supports previous findings that inhibitor development in non‐severe haemophilia needs to be seriously considered (van Velzen et al , ; Fischer et al , ). Comprehensive results are presented from a retrospective audit and evaluation of treatment patterns, haemostatic strategies, F8 genotyping and inhibitor screening practices in a large cohort of patients with non‐severe haemophilia A from seven centres in the London region (Batty et al , ).…”
supporting
confidence: 62%
“…However, standardization of PHT to optimize inhibitor screening contributes to the ongoing discussion about the importance of implementing validated systematic inhibitor screening practices in congenital haemophilia. These screening practices are well established in severe haemophilia during initiation of treatment, but less so in nonsevere haemophilia . It is likely that PHT is of more relevance in testing of samples from patients with nonsevere haemophilia A, given the presence of FVIII:C, sporadic peak‐treatment moments and lifelong inhibitor risk or in patients with severe haemophilia A undergoing immune tolerance induction, thus avoiding the need for a washout period prior to testing.…”
Section: Discussionmentioning
confidence: 99%
“…These screening practices are well established in severe haemophilia during initiation of treatment, 20 but less so in nonsevere haemophilia. 21 It is likely that PHT is of more relevance in testing of samples from patients with nonsevere haemophilia A, given the presence of FVIII:C, sporadic peaktreatment moments and lifelong inhibitor risk 22 nonsevere haemophilia A setting, knowledge of a low-titre inhibitor present using a PHT-optimized assay in an appropriately timed post-treatment, "convalescent" inhibitor screen, 21 may inform both the treating physician and patient in preparation for future treatment. This is of importance given greater than 50% of inhibitory antibodies in nonsevere HA are reported to cross-react with endogenous FVIII, reducing the FVIII:C baseline and worsening bleeding phenotype.…”
Section: Pre-analytical Heat Treatment In Congenital and Acquired Hmentioning
confidence: 99%